Decentralisation, local communities and forest management in Barito Selatan district, Central Kalimantan - McCarthy, J.F. (Center for International Forestry Research, 2001)
Based on field research carried out in Central Kalimantan during June and July 2000, this chapter examines the likely impact of the decentralisation reforms on forest management in Barito Selatan. Conclusions are derived from three major sources. First, interviews were conducted with key government officials and community figures in the provincial capital, Palangkaraya, and the district capital, Buntok. These were supplemented with information from relevant newspaper and government reports. Thirdly, brief visits were made to a number of communities around the district to examine the implications of these reforms for forest dependent communities and to consider the degree to which local communities are likely to benefit from the new decentralised arrangements. The first section of this chapter provides an overview of the geographic and economic context, at the same time discussing the forestry sector in the district. The second section examines specific disputes, controversies and decisions regarding land use, forestry regulations, law enforcement, and revenue collection, considering the roles and motivations of different stakeholders during the decentralisation process and the consequent implications for forests and people. The third section considers the situation of forest dependent communities in the district in the midst of the decentralisation process. It examines the fate of village communities dependent on rattan gardens, the circumstances of an isolated and impoverished community living in the middle of a logging concession area, and a hamlet where eleven unlicensed sawmills had opened operations over the previous twelve months. Based on this discussion, the final section draws some conclusions regarding the real and anticipated effects of decentralisation on forest management in the district.